EXPLORING THE IMPACT OF LOCAL FOLKLORE ON STUDENTS’ READING COMPREHENSION SKILLS: A MIXED METHOD STUDY - Sopian, Sopian; Pujianto, Eko; Purwaningsih, Lilik; Hanafi, Imam (Universitas Jambi, 2025)
This study explores the reading comprehension skills of junior high school students by using local folklore texts as reading material. Local folklore is a culturally rich and engaging medium that enhances students’ understanding of narrative structures, vocabulary, and moral values. The research aims to examine the level of students’ reading comprehension and how local culture-based texts can be effectively integrated into reading lessons. The study uses a quantitative approach, including reading tests based on one local folklore, an interview sheet, and observations. The subjects of the research were 50 eighth-grade students from two classes at a private school in Indonesia. The analysis of pre-test and post-test scores revealed a significant improvement in reading comprehension for the experimental group. The mean post-test score for the experimental group was 15% higher than the pre-test score, indicating that exposure to local folklore had a positive effect on students' comprehension abilities. Findings indicate that folklore texts positively influence students’ comprehension, particularly in identifying main ideas, interpreting implicit meanings, and relating texts to personal experiences. This supports the integration of local literature in language learning to promote cultural literacy and comprehension skills.